Desmaterialización de títulos valores con Blockchain aplicado a cheques (2020)
The purpose of this project is to dematerialize checks using Hyperledger Sawtooth, in order to fix many of today's check-related problems. For this reason, an architecture was proposed and it was also implemented in an application that meets the legal requirements of checks. An MVP (Minimum Viable Product) was also created that shows and validates the solution in addition to complying with legal requirements.--Taken from the Degree Document Format.